2012
DOI: 10.11606/issn.2176-7262.v45i1p23-30
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional avaliado por medidas antropométricas em pré-escolares atendidos pelo Programa de Saúde da Família de Ribeirão Preto - SP

Abstract: Design of the study: survey cross sectional Objectives: To assess the nutritional status of preschool children using anthropometric measurements. Methods: Anthropometric data for weight, height, skinfolds and circumferences and anthropometric data of the birth and breastfeeding from a representative sample of preschool children aged between 2 and 5 years, of both sexes, belonging to families enrolled in Family Health Program linked to the Health Care Center/University of São Paulo at Ribeirão Preto School of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Four articles 23 , 24 , 25 , 26 involving sample sizes ranging from 155 23 to 443 25 children were included. Stunting was evaluated in only two studies and showed prevalence rates of 6.3% 25 and 9.7%.…”
Section: Resultsmentioning
confidence: 99%
“…Four articles 23 , 24 , 25 , 26 involving sample sizes ranging from 155 23 to 443 25 children were included. Stunting was evaluated in only two studies and showed prevalence rates of 6.3% 25 and 9.7%.…”
Section: Resultsmentioning
confidence: 99%